Need for Achievement as a Predictor of Entrepreneurial Behavior: The Mediating Role of Entrepreneurial Passion for Founding and Entrepreneurial Interest - Saif, Haroon A.A.; Ghania, Usman (International Review of Management and Marketing, 2019)
This study aims to explore the role of new predictors of Entrepreneurial behavior (EB). Build on entrepreneurial passion literature we propose that entrepreneurial passion for founding (EPF) predicts EB. We then apply McClelland’s (1961) Need for achievement (NACH) theory to propose that NACH predicts EB. We also propose that EPF and entrepreneurial interest mediate this relationship. Furthermore, we hypothesize that prior experience moderates EPF and EB relationship as well as NACH and EB relationship and EI and EB relationship. Based on a sample of 223 collected by using a reliable questionnaire distributed to actual and potential entrepreneurs from different nationalities who are living in china; we found support for our hypotheses. Results indicated that EPF and NACH are significantly related to EB. Furthermore, we found that entrepreneurial interest and EPF mediate NACH and EB relationship. Moreover, the results revealed that prior experience affects the relationship between EPF and EB and NACH and EB as well as the relationship between entrepreneurial interest and EB such that prior experience strengthens those relationships. Study implications, limitations, and future directions are discussed. Keywords: Entrepreneurial Behavior, Entrepreneurial Interest, Entrepreneurial Passion, Need for Achievement, Prior Experience JEL Classifications: L26, J52 DOI: https://doi.org/10.32479/irmm.8949